Psychological Features of Significance and Satisfaction of Civil Service Employees’ Professional Motives with Different Seniority and Experience in the Executive Bodies - Malymon, Liudmyla; Glova, Iryna (Psychological Prospects Journal, 2014)
The article deals with professional motivation of civil servants of local authorities. The authors have analyzed professional motives in terms of their personal importance for an employee and their accessibility (satisfaction) in his professional activity. The theoretical analysis of these motive features’ correlation has defined the areas of potential motive motivational discomfort and stress, which can trigger the development of internal conflict or emptiness in public service employees and be manifested in their behavior in various forms of passive or active resistance, rejection of senior managers’ demands and instructions, etc. The results of the analysis of the indicators of the Sh. Ritchie-P. Martin test show the availability of the public service employee personality motivational hierarchy and his professional motives diversity based on four types of relationships between the desired and current state of motives: «significant–realized», «significant–unrealized», «insignificant–realized», and «insignificant–unrealized». Statistic methods uncovered showed deviations between the importance and satisfaction of all professional motives (except «structured work» motive) for the workers with different seniority. It is argued that among the most realizable are motives related to the specifics of the civil servants’ activity and characterize procedural and executive motivation (job content, compliance with the administrative requirements and job descriptions). Finally, a group of key motives viewed as personally significant, albeit unrealized in the career, have been found, such as: salary, working conditions, recognition, self-improvement, creativity. It is proved that personal importance and satisfaction of professional motives determine their hierarchy, strength and stability at the various stages of professional activity, thereby providing a deterministic impact on its efficiency.